Addams family values [videorecording (DVD)] - Sonnenfeld, Barry; Julia, Raul; Huston, Anjelica; Lloyd, Christopher, 1938-; Ricci, Christina; Cusack, Joan, 1962-; Addams, Charles, 1912-1988 (Warner Home Video, 2013)
The adventures of the Addams family continue, when Uncle Fester gets married to a murderous socialite, and Gomez and Morticia have another baby.